Design of Ultra-Wide Band Tapper Rectangular Patch Monopole Antenna for Terahertz Applications - Hussein Abdulnabi; Ahlam Alsudani; Yasin Yousif Al-Aboosi; Mariam Qutaiba Abdalrazak; Haider Ali Abdulnabi; Mustafa Mahdi Ali (Journal of Engineering and Sustainable Development, 2025)
In this paper, an ultra-wideband terahertz monopole antenna is proposed to address the limitations of lower bandwidth and low gain in previously designed antennas at THz frequencies. The antenna is composed of three parts: a pentagonal patch, a modified ground plane that provides impedance matching (2.5-12) THz, and an FR-4 material substrate. The complete proposed antenna has been simulated using electromagnetic software and a computer simulation tool. Based on the simulation findings, the proposed antenna is the best option for Tera-Hertz applications. The antenna has an acceptable gain in the intended frequency spectrum band and operates between 2.4 and 12 THz. Computer simulation technology (CST 2020) software has been used to Analyze and simulate the proposed antenna. The simulation results show that the return losses of the frequency band (2.4-12) THz are less than -10 dB, and the gain has an appropriate value over the frequency band 2.4-12) THz. The radiation pattern of the antenna is omni-direction at the desired frequency band.